2016
DOI: 10.18632/oncotarget.6852
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miR-101 contributes to epithelial-mesenchymal transition in cisplatin resistance of NSCLC cells by targeting ROCK2

Abstract: Chemoresistance and epithelial-mesenchymal transition (EMT) in cancer are linked phenomena. EMT contributes to chemoresistance, however, little is known about whether chemotherapy can induce EMT in cancer cells. Here, we found that miR-101 expression was downregulated in cisplatin-resistant non-small cell lung cancer (NSCLC) cells. Restoration of miR-101 expression inhibited EMT and increased the sensitivity of cisplatin-resistant NSCLC cells to cisplatin in vitro by targeting ROCK2. Furthermore, ROCK2 protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 30 publications
2
36
0
Order By: Relevance
“…Accumulating researches had reported that the abnormal expression of miR-101 was involved in cell proliferation, colony formation, migration and apoptosis through targeting some genes [21,22]. Given its signi cant functions in controlling the biological behaviors of tumor cells, miR-101 was considered as a promising candidate bio-marker for therapy and prognosis of some cancers [23,24]. For examples, the study of Li et al reported that the expression of miR-101 was decreased in laryngeal squamous cell carcinoma tissues, and showed negative association with high tumor grade, lymph node metastasis as well as advanced clinical stage [25].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating researches had reported that the abnormal expression of miR-101 was involved in cell proliferation, colony formation, migration and apoptosis through targeting some genes [21,22]. Given its signi cant functions in controlling the biological behaviors of tumor cells, miR-101 was considered as a promising candidate bio-marker for therapy and prognosis of some cancers [23,24]. For examples, the study of Li et al reported that the expression of miR-101 was decreased in laryngeal squamous cell carcinoma tissues, and showed negative association with high tumor grade, lymph node metastasis as well as advanced clinical stage [25].…”
Section: Discussionmentioning
confidence: 99%
“…Cancer cells can hijack signaling by over-expressing or mutating growth factor receptors to increase proliferative signals and miRNAs target certain receptor to modulate signaling. [187][188][189][190][191][192] let-7c-5p Decreased N/K-RAS, ABCC2, Bcl-XL, ITGB3, MAP4K3, HOXA1 [122,[193][194][195][196] miR-101-3p Decreased ZEB1, ROCK2, MALAT-1, EZH2 [48,180,[197][198][199] target epidermal growth factor (EGFR) (Figure 3), which is commonly overexpressed in NSCLC (Table 1), to alter downstream signaling molecules such as AKT and ERK1/2 and decrease the growth phenotype. In addition, miR-139-5p, 58 miR-30a-5p, 59 miR-140-3p, 60 miR-320a-3p 61 and miR-195-5p 62 all target insulin-like growth factor 1 receptor (IGF1R), while miR-486-5p directly targets both IGF1R and its ligand insulin-like growth factor 1 (IGF1) 63 and miR-135a-5p targets only IGF1.…”
Section: Signal Transduction In Lung Cancer Survival and Proliferationmentioning
confidence: 99%
“…9 Furthermore, miRNAs play a critical role in various cancer cellular processes, such as development, proliferation, apoptosis, migration, invasion, and drug resistance. 10 To identify the biological role of miRNAs in gefitinibresistant cells, we examined the genome-wide miRNA expression in the parental HCC827 cells and gefitinibresistant HCC827/GR-8-1 cells. Previous studies showed that miRNAs regulate the EGFR gene pathway and are a predictor of response to EGFR-tyrosine kinase inhibitor (TKI) therapy in cancer.…”
Section: Micro-rna and Lung Cancermentioning
confidence: 99%